Sexuality - Bristow, Joseph (Routledge, 1997)
Joseph Bristow introduces readers to the most influential contemporary theories of sexual desire and reveals how nineteenth century scientists invented 'sexuality'. This clear and fascinating introductory guide makes complex theoretical ideas accessible to readers of all levels. It explores: the lasting influence of late-Victorian sexology conflicting accounts of eroticism the place of Freud and Lacan within cultural studies, literary criticism and feminist theory the importance of Bataille, Baudrillard, Cixous, Deleuze, Irigaray and Kristeva the legacy of Michel Foucault in queer theory today postmodern sexual identities, and the contemporary emphasis on erotic diversity